Toxoplasmosis Outbreak Associated With Toxoplasma gondii-Contaminated Venison—High Attack Rate, Unusual Clinical Presentation, and Atypical Genotype. (15th May 2020) - Schumacher, Amy C; Elbadawi, Lina I; DeSalvo, Traci; Straily, Anne; Ajzenberg, Daniel; Letzer, David; Moldenhauer, Ellen; Handly, Tammy L; Hill, Dolores; Dardé, Marie-Laure; Pomares, Christelle; Passebosc-Faure, Karine; et al.
Abstract: Background: During 2017, in response to a physician's report, the Wisconsin Department of Health Services, Division of Public Health, began investigating an outbreak of febrile illness among attendees of a retreat where never frozen, intentionally undercooked, locally harvested venison was served. Preliminary testing tentatively identified the illness as toxoplasmosis. Methods: Confirmatory human serology panels and testing of the venison to confirm and categorize the presence and type of Toxoplasma gondii were completed by French and American national reference laboratories. All 12 retreat attendees were interviewed; medical records were reviewed. Results: All attendees were male; median age was 51 years (range: 22–75). After a median incubation period of 7 days, 9 (82%) of 11 exposed persons experienced illness lasting a median of 12 days. All 9 sought outpatient healthcare for symptoms including fever, chills, sweats, and headache (100%) and ocular disturbances (33%). Testing confirmed the illness as toxoplasmosis and venison as the infection source. Multiple laboratory results were atypical for toxoplasmosis, including transaminitis (86%), lymphocytopenia (88%), thrombocytopenia (38%), and leukopenia (63%). One exposed but asymptomatic person was seronegative; the other had immunity from prior infection. The T. gondii strain was identified as closely related to an atypical genotype (haplogroup 12, polymerase chain reaction restriction fragment length polymorphism genotype 5) common in North American wildlife but with previously uncharacterized human clinical manifestations. Conclusions: The T. gondii strain contaminating the venison might explain the unusual clinical presentations. In North America, clinicians and venison consumers should be aware of risk for severe or unusual presentations of acute toxoplasmosis after consuming undercooked game meat. Abstract : Venison contaminated with a Toxoplasma gondii strain related to haplogroup 12 (atypical, common in North American wildlife) was confirmed as the source of a toxoplasmosis outbreak among a group of immunocompetent men with high attack rate and unusual clinical presentation.